Utilization of omega-3 fatty acids is improved by embedding flaxseed in a matrix of dolomitic lime hydrate - Christian A. Alvarado-Gilis; Cadra L. Van Bibber-Krueger; K. A. Miller; E. San Vito; G. Feltrin; D. Klamfoth; James S. Drouillard (Kansas Agricultural Experiment Station Research Reports, 2014)
Omega-3 fatty acids are essential nutrients for humans, but American diets are often deficient in these important long-chain fats. Incorporating greater proportions of omega-3 fatty acids into beef offers a means of increasing daily consumption of essential fats, while also enhancing the perceived value of beef. In cattle, dietary polyunsaturated fats are extensively hydrogenated into saturated fats by microbes in the rumen. This effectively decreases the efficiency of transfer for fats from the animal's diet into edible beef tissues, because the bacteria convert more than 90% of the polyunsaturated fats into saturated fats before they are absorbed into the animal's blood stream. Preventing this saturation process in the rumen would increase the proportion of dietary omega-3 fatty acids that are available for deposition into beef, thus making the production of omega-3-enriched beef more cost-effective. We have devised a method for improving the stability of fats in the rumen that effectively increases their resistance to the hydrogenating actions of rumen microbes. Sources of polyunsaturated fats are combined with dolomitic lime hydrate, water is added, and the mixture is blended at a high rate of rotation, yielding a densified matrix with improved ruminal stability. Our objective in this study was to evaluate feedlot performance, carcass characteristics, and blood profiles of long-chain fatty acids in cattle fed diets containing varying concentrations of ground flaxseed or ground flaxseed embedded in the dolomitic lime matrix.
Keywords: Cattlemen& #x27; s Day; 2014; Kansas Agricultural Experiment Station contribution; no. 14-262-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 1101; Beef Cattle Research; 2014 is known as Cattlemen& #x27; s Day; Beef; Omega-3 fatty acids; Rumen; Carcass traits